PHYSICOCHEMICAL ANALYSIS OF ARABICA COFFEE SIGARAR UTANG VARIETIES BASED ON VARIATIONS OF PROCESSING METHODS (FULLYWASH, HONEY, AND NATURAL PROCESS) - Kurniawan, Muhammad Fakih; Aminah, Siti; Agusthini, Trie Lely (Jurnal Pangan dan Agroindustri, 2024)
Coffee is processed with a variety of processes such as natural (dry), fullywash (wet), and honey processes. The type of coffee processing influences the characteristics of the coffee produced. The aim of this research is to analyze the physicochemical characteristics of the Sigarar Utang variety of arabica coffee based on different processing methods (fullywash, honey and natural process). The research design used a one-factor Completely Randomized Design (CRD). The research results showed that the type of coffee processing method had a significant effect on water content, coffee essence content, sucrose content, total dissolved solids (TDS), total titratable acidity (TTA), pH, total phenols and antioxidant activity of coffee brewing, but had no significant effect on ash content. The test results for water content, ash content and coffee essence content are in accordance with the Indonesian National Standard (SNI) for coffee powder. Coffee with honey processing has high values ​​for water content, sucrose content, and TDS, while coffee with fullywash processing has the highest acidity, total phenols and antioxidant activity.